Pengaruh Pengawasan, Disiplin dan Motivasi Kerja terhadap Produktivitas Kerja Pegawai Toserba Yogya Sukabumi - Wikeu Tsnia Fariati (JURNAL BUANA INFORMATIKA CBI, 2017)
In general, productivity is defined as the relationship between the real anf physical ( good or services 0 with the actual input. Or in other words, productivity is a measure of produvtive efficiency. A comparison between the output and input or output divided by input, as you well know, there are some important factors that can determine the goals and improve employee productivity, namely supervision, discipline an motivation to work. The purpose of this study was to determine the effect of simultaneous delivery of supervision, discipline and motivation to work on the productivity of employees working Toserba Yogya Sukabumi, to determine the effect of partial supervision, discipline and motivation to work on the productivity working in Toserba Yogya Sukabumi. This research method is a quantitative research study that is based on data in this form of numbers – the numbers are processed by statistical analysis for influence between variable and sample use are as many as 77 sample. Testing instrument to test the validity an d realiability. Statistical method of data analysis to help management with the program SPSS ( Statistic Packag for Soail Science ). The result showed that the regression equation is obtained as follow : Y = 0.131 + 0.245X1 + 0.594 X2 + 0.16+2 X3. Effect of control ( X1), the discipline of work (X2), and work motivation (X3) together on the productivity of labor ( Y) is shown by regression of X1, X2 and X3 to Y at r = 0.864. Between the influence of the control (X1), the discipline of the work (X2), and work motivation (X3) on labor productivity ( Y) very strong and its influence + ( positive) meaning that the higher supervision (X1), the discipline of work (X2) and work motivation (X3) it al;so increases labor productivity ( Y ) in Toserba Yogya Sukabumi. Keywords : Supervision, discipline and work motivation on employee productivity